Diseño de ambientes de aprendizaje virtual en tercera dimensión en la Universidad de la Costa (2016)
The content of this project is based on the design of virtual learning environments in three dimensions, installation, configuration, and its applicability in digital circuits. The configuration of OpenSimulator software it explains step by step, which is software to create 3D virtual worlds and in the same way, it shows the settings of a viewer software necessary to represent the virtual learning environment in three dimensions. There are explanations of the guidelines that must be made, in a tutorial mode, with images, and text that describing instructions. To finally, create, and implement a virtual learning environment in third dimension in where students can browse, interact, and pretend as if they were in a real university using digital circuits.